2020
DOI: 10.3390/app10145000
|View full text |Cite
|
Sign up to set email alerts
|

Task Planning of Space-Robot Clusters Based on Modified Differential Evolution Algorithm

Abstract: This study studies the problem of on-orbit maintenance task planning for space-robot clusters. Aiming at the problem of low maintenance efficiency of space-robot cluster task-planning, this study proposes a cluster-task-planning method based on energy and path optimization. First, by introducing the penalty-function method, the task planning problem of the space-robot cluster under limited energy is analyzed, and the optimal-path model for task planning with comprehensive optimization of revenue and energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Vesterstrom et al [205] conducted the experiments over numerical benchmarks and demonstrated the DE has a better performance compared to GA and PSO. For the robot task planning problem, Xiao et al [206] modified the DE algorithm by combining the roulette and multi-neighborhood operations (to solve local optimal solution), the de-crossover strategy (to increase the convergence speed), and the multi-population integration strategy (to get high computing resources). The DE optimal path model could provide good performance as compared to the shortest path model under limited energy usage.…”
Section: ) Genetic Evolutionmentioning
confidence: 99%
“…Vesterstrom et al [205] conducted the experiments over numerical benchmarks and demonstrated the DE has a better performance compared to GA and PSO. For the robot task planning problem, Xiao et al [206] modified the DE algorithm by combining the roulette and multi-neighborhood operations (to solve local optimal solution), the de-crossover strategy (to increase the convergence speed), and the multi-population integration strategy (to get high computing resources). The DE optimal path model could provide good performance as compared to the shortest path model under limited energy usage.…”
Section: ) Genetic Evolutionmentioning
confidence: 99%
“…A navigation architecture becomes efficient if the mobility of the robot is divided into specialized software modules. This architecture consists of software modularity (as a consequence of introducing a new sensor or maintaining some obstacle avoidance modules based on certain cinematics), robot location control based on the different functionalities and learning algorithms, techniques of time-domain analysis (response time of the sensors, temporal depth, space localization, and decision making based of the dynamics of the robot), and decoupled control [ 32 , 33 , 34 , 35 , 36 ]. Implementing machine learning and deep learning techniques requires precise information so that the path planning allows locating the robot in space and memorizing the position of obstacles.…”
Section: Configuration Of the Intervention Robotmentioning
confidence: 99%